Anti-Inflammation Effects of Silver Nanoparticles-Zinc Polycarboxylate Cement (AGNPS-ZPCCEM) - Aneer Emad, Entisar E. Al-Abodi (Pakistan Journal of Medical & Health Sciences, 2022)
Though, zinc polycarboxylate cement(ZPCCEM) is a good root filling block of cement, But its efficiency against microbes was low or non-existent.ThE purpose Of our studying is Evaluation of the effects of adding silver nanoparticles to the (S-NP) to (ZPCCEM), on antimicrobial effectiveness towards the three Microorganisms appear in human infection, including, Escherichia-coli (E.-coli) are a Gram-negative, Staphylococcus-aureus (S.aureus) is a Gram-positive round-shaped bacterium, a member of the Bacillota, and Candida albicans It appears to be used as an organism for fungal pathogens, these microorganisms are of the most prevalent taxa, that caused Chronic periodontitis and pulpitis Combined 4g of powder zinc polycarboxylate cement with 3 drops of liquid zinc polycarboxylate cement to give zinc polycarboxylate cement(ZPCCEM) and mixed with various amounts of Silver nanoparticles powder to give (AgNPs-ZPCCEM) composites. The diagnosis of AgNPs, (ZPCCEM) and (AgNPs-ZPCCEM) were carried out with FTIR and FESEM analysis. To evaluate the antimicrobial effectiveness, agar diffusion and broth dilution methods were used. In the agar diffusion test, (ZPCCEM) And (AgNPs-ZPCCEM), showed zones of inhibition against three microorganisms. The (AgNPs-ZPCCEM), showed the most superior synergy with (AgNPs-ZPCCEM). The activity of the (AgNPs-ZPCCEM) and cement alone was increased up to 28 and 35 mm against E-coil respectively, against Staphylococcus aureus. Similarly, the antimicrobial activity of (AgNPs-ZPCCEM) and cement alone was shown at 23 and 31 mm respectively, while the antimicrobial activity of (AgNPs-ZPCCEM) and cement alone was 15 and 12 mm respectively, against Candida albicans.